2006
DOI: 10.1111/j.1365-2869.2006.00493.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue and shift work

Abstract: Summary Shift work is a ubiquitous phenomenon and its adverse effects on workers’ physical and mental health have been documented. In the sleep literature, differentiating between the symptoms of fatigue and sleepiness, and developing appropriate objective and subjective measures, have become very important endeavors. From such research, fatigue and sleepiness have been shown to be distinct and independent phenomena. However, it is not known whether shift work differentially affects fatigue and sleepiness. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
61
1
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(78 citation statements)
references
References 17 publications
(31 reference statements)
11
61
1
5
Order By: Relevance
“…Fatigue that results in excessive sleepiness while at work may manifest as weariness, difficulty concentrating, headache, irritability or depressed mood, and feeling unrefreshed after sleeping. 42 …”
Section: Hospitalists and Night Shiftsmentioning
confidence: 99%
“…Fatigue that results in excessive sleepiness while at work may manifest as weariness, difficulty concentrating, headache, irritability or depressed mood, and feeling unrefreshed after sleeping. 42 …”
Section: Hospitalists and Night Shiftsmentioning
confidence: 99%
“…According to the U.S National Transportation Safety Board Report, 57% of the accidents were due to fatigue 10) . In another study carried out by J. Shen shift workers encountered more fatigue than non shift workers, but there was no much difference between the severities of sleepiness for the two groups 11) . Knowledge about the influence of shift works on fatigue and sleep disturbances are still limited.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found an association between shift work and general mental health (1-3), psychological well-being (4-6), irritability/ irritation/strain (7), and severe emotional problems (8). Studies have also shown that shift workers experience depression to different degrees [ie, major depressive disorder (9,10), sub-clinical depression (11)], general malaise including depression and anxiety elements (12), higher levels of burnout (13), more fatigue (7,14,15), and mental tiredness (16). However, most of these studies were cross-sectional, with limited potential to demonstrate causal relationships.…”
mentioning
confidence: 99%